Corporate Governance, Investor Protection, and Performance in Emerging Markets - Klapper, Leora F.; Love, Inessa (World Bank, Washington, D.C., 2013)
Recent research studying the link between law, and finance has concentrated on country-level investor protection measures, and focused on differences in legal systems across countries, and legal families. The authors extend this literature, and provide a study of firm-level corporate governance practices across emerging markets, and a greater understanding of the environments under which corporate governance matters more. Their empirical tests show that better corporate governance is highly correlated with better operating performance, and market valuation. More important, the authors provide evidence showing that firm-level corporate governance provisions, matter more in countries with weak legal environments. These results suggest that firms can partially compensate for ineffective laws, and enforcement by establishing good governance, and providing credible investor protection. The authors' tests also show that firm-level governance, and performance is lower in countries with weak legal environments, suggesting that improving the legal system, should remain a priority for policymakers.